Strategic Planning Update - Leonard A. Brennan (National Quail Symposium Proceedings, 2017)
This paper is a snapshot assessment of what has been achieved in quail management and research since the first national strategic planning workshop was organized at Quail III in 1992. In general, interest in quail remains strong and in many cases is increasing, among a diverse community of managers, researchers, and hunters, despite the continued population declines of several species of quails, and widespread loss of quail hunting opportunities on both public and private lands. Several regional interest groups who serve as advocates for quail have emerged in both the southeastern and western U.S. Some potentially promising opportunities for broad scale habitat improvement have emerged from Farm Bill legislation (such as subsidies for planting longleaf pine [Pinus palustris] in the Southeast). Whether such incentives will serve to reverse the broad scale northern bobwhite decline, remains to be seen. Several states in both the Southeast and Midwest have either reaffirmed or renewed their commitment to quail research and management. They fully realize that reversing declines and local extinctions will be extremely difficult given the incompatibility between most modem agricultural and forestry land use practices and the habitat needs of wild quail. How, and if, wild quail will be able to fit within the ever-tightening constraints of modem land use by our prodigal society is one of the most challenging questions currently facing anyone interested in these birds.